2015
DOI: 10.1590/1414-431x20143969
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of estrogen and oxytocin receptors in the uterus of pregnant and parturient bitches

Abstract: In the canine species, the precise mechanisms of pregnancy maintenance and the initiation of parturition are not completely understood. The expression of genes encoding the receptors for estrogen (ERα mRNA) and oxytocin (OTR mRNA) was studied in the endometrium and myometrium during pregnancy and parturition in dogs. Real-time PCR was performed to quantify the levels of ERα mRNA and OTR mRNA in the uterus of bitches during early (up to 20 days of gestation), mid (20 to 40 days) and late pregnancy (41 to 60 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
2
15
0
1
Order By: Relevance
“…Until now, the mechanism that triggers such changes in dogs is unknown, as longitudinal studies along the periods of pregnancy and parturition are scarce. In previous works, we have observed that both endometrial ERα mRNA and OTR mRNA remained unchanged until late pregnancy, but the expression of OTR mRNA in canine uterine tissues (endometrium and myometrium) varied over time (Veiga et al, 2015). Additionally, we have shown that the canine CL does not express ERα mRNA during pregnancy, whereas a decreased profile of OTR mRNA expression occurs (Veiga et al, 2014).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Until now, the mechanism that triggers such changes in dogs is unknown, as longitudinal studies along the periods of pregnancy and parturition are scarce. In previous works, we have observed that both endometrial ERα mRNA and OTR mRNA remained unchanged until late pregnancy, but the expression of OTR mRNA in canine uterine tissues (endometrium and myometrium) varied over time (Veiga et al, 2015). Additionally, we have shown that the canine CL does not express ERα mRNA during pregnancy, whereas a decreased profile of OTR mRNA expression occurs (Veiga et al, 2014).…”
Section: Introductionmentioning
confidence: 65%
“…Sample tubes without placenta tissue were used for negative controls. No positive controls were adopted, however primers were previously standardized and simultaneously employed for amplification in other canine tissue samples (endometrium, myometrium and corpus luteum), which revealed positive amplifications (Veiga et al, 2014;2015). All reactions were performed in a total volume of 25 µL and heated to 50°C for 2 min and then 95°C for 10 min followed by 45 cycles comprising denaturation at 95°C for 15 sec and then annealing for 60 sec at the following temperatures: 61°C for RPS5, 60°C for 18S and 59°C for ERα and OTR.…”
Section: Real-time Pcr Amplificationmentioning
confidence: 99%
“…In this study, we examined the local production of OXT and its regulation in human placenta. It is known that OXT levels in the blood increase during pregnancy (Thornton et al 1992, Veiga et al 2015, which was also Immunostaining of OXT and OXTR in human placental tissue. To examine localization of each protein, tissues were stained with specific antibodies for OXT (A) and OXTR (B).…”
Section: Discussionmentioning
confidence: 93%
“…For example, in rats, the epithelial cells of the uterus can synthesize oxytocin ________________________________________________________________________________ ________________________________________________________________________________ Habib et al (2020) (Jarrett et al 2006). Furthermore, there is an indirect relationship between oxytocin and product of prostaglandins F2a (PGF2a) from endometrial cells (Veiga et al 2015).…”
Section: Uterusmentioning
confidence: 99%